Heritability and Familiality of Temperament and Character Dimensions in Korean Families with Schizophrenic Linkage Disequilibrium - Lee, Byung Dae; Park, Je Min; Lee, Young Min; Moon, Eunsoo; Jeong, Hee Jeong; Chung, Young In; Yi, Young Mi (Clinical psychopharmacology and neuroscience : the official scientific journal of the Korean College of Neuropsychopharmacology, 2016)
Categorical syndromes such as schizophrenia may represent complexes of many continuous psychological structural phenotypes along several dimensions of personality development/degeneration. The present study investigated the heritability and familiality of personality dimensions in Korean families with schizophrenic linkage disequilibrium (LD). We recruited 179 probands (with schizophrenia) as well as, whenever possible, their parents and siblings. We used the Temperament and Character Inventory (TCI) to measure personality and symptomatic dimensions. The heritability of personality dimensions in a total of 472 family members was estimated using Sequential Oligogenic Linkage Analysis Routines (SOLAR). To measure familiality, we compared the personality dimensions of family members with those of 336 healthy unrelated controls using analysis of variance (ANOVA) analysis. Three of the seven TCI variables were significantly heritable and were included in subsequent analyses. The three groups (control, unaffected first-degree relative, case) were found to significantly differ from one another, with the expected order of average group scores, for all heritable dimensions. Despite several study limitations with respect to family recruitment and phenotyping, our results show that aberrations in several personality dimensions related to genetic-environment coactions or interactions may underlie the complexity of the schizophrenic syndrome.